National Medical Expenditure Survey, 1987: Household Survey Data on Home Health Care and Medical Equipment Purchases and Rentals (Public Use Tape 14.2) ([Verlag nicht ermittelbar], 1993)
The 1987 NMES provides information on health expenditures by or on behalf of families and individuals, the financing of these expenditures, and each person's use of services. The Household Survey is one of the three major components of the 1987 National Medical Expenditure Survey (NMES). (The other two components are the Survey of American Indians and Alaska Natives [SAIAN] and the Institutional Population Component.) The Household Survey was fielded over four rounds of personal and telephone interviews at four-month intervals. Baseline data on household composition, employment, and insurance characteristics were updated each quarter, and information on all uses of and expenditures for health care services and sources of payment was obtained. Public Use Tape 14.2 provides two data files containing information on expenditures for formal home health care and the purchase or rental of medical equipment, supplies, and other medical items. The Home Health Care file contains information on each person in the Household Survey using these services in 1987. Each record is restricted to the set of formal services provided during the year by each type of provider sent by each unique agency furnishing home health care. This file provides person-level demographic information such as age, sex, and race, and information on household-reported medical conditions associated with the use of home health care. The Medical Equipment and Supplies file contains one record per type of medical item for each eligible person in the Household Survey who reported having purchased, rented, or otherwise obtained such items. This file also provides person-level demographic information, and medical condition and date of purchase variables.